2023
DOI: 10.1002/adhm.202300890
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetyl‐l‐cysteine‐Derived Carbonized Polymer Dots with ROS Scavenging via Keap1‐Nrf2 Pathway Regulate Alveolar Bone Homeostasis in Periodontitis

Abstract: Periodontitis is a type of chronic inflammatory oral disease characterized by the destruction of periodontal connective tissue and progressive alveolar bone resorption. As oxidative stress is the key cause of periodontitis in the early periodontal microenvironment, antioxidative therapy has been considered a viable treatment for periodontitis. However, more stable and effective reactive oxygen species (ROS)‐scavenging nanomedicines are still highly needed due to the instability of traditional antioxidants. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Furthermore, our previous investigation showed Metronidazole-derived carbon dots featuring selective antibacterial activity and fluorescent properties, essential for periodontal disease treatment, offering prospects for addressing other bacterial-driven diseases . In our recent research, carbonized polymer dots derived from N -acetyl- l -cysteine were found to exhibit mitochondrial colocalization and a specific enrichment in periodontal tissues, facilitating the exertion of their antioxidant therapeutic effects . These studies collectively underscore the advantages and potential of carbon dots for the therapy of periodontitis.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, our previous investigation showed Metronidazole-derived carbon dots featuring selective antibacterial activity and fluorescent properties, essential for periodontal disease treatment, offering prospects for addressing other bacterial-driven diseases . In our recent research, carbonized polymer dots derived from N -acetyl- l -cysteine were found to exhibit mitochondrial colocalization and a specific enrichment in periodontal tissues, facilitating the exertion of their antioxidant therapeutic effects . These studies collectively underscore the advantages and potential of carbon dots for the therapy of periodontitis.…”
Section: Introductionmentioning
confidence: 77%
“…38 In our recent research, carbonized polymer dots derived from Nacetyl-L-cysteine were found to exhibit mitochondrial colocalization and a specific enrichment in periodontal tissues, facilitating the exertion of their antioxidant therapeutic effects. 39 These studies collectively underscore the advantages and potential of carbon dots for the therapy of periodontitis.…”
Section: Introductionmentioning
confidence: 91%
“…These techniques are capable of introducing cationic segments, such as N,N ′-dimethylamino-2-ethyl methacrylate (DMAEMA), 2-( tert -butylamino)ethyl methacrylate, and amino butyl methacrylate, into the polymer backbone to realize antibacterial activities. 170 Takahashi synthesized a cationic methacrylate copolymer with amino butyl methacrylate as the antibacterial segment (Fig. 10a).…”
Section: Antimicrobial Polymeric Materials To Combat the Oral Biofilmmentioning
confidence: 99%
“…23). 170 Cysteine is a widely used antioxidant. By constructing NAC-CPDs through formamide-assisted solvothermal reaction, the stability of NAC was greatly improved than when it was encapsulated into carriers.…”
Section: Anti-inflammatory Polymeric Materials To Overcome the Oral I...mentioning
confidence: 99%
“…LPS can stimulate the generation of proinflammatory cytokines, which provoke and sustain immune cell recruitment and activation as well as tissue damage in periodontal tissues ( Han et al, 2022 ). Concurrently, oxidative stress causes direct harm to cells and tissues, leading to further tissue damage, as well as inflammatory responses that increase the microbial dysbiosis ( Liu et al, 2023 ). Cumulatively, the shift towards an anaerobic Gram-negative bacterial community, along with the presence of LPS and oxidative stress, act synergistically to promote chronic inflammation and to foster the exacerbation of periodontal diseases ( Willmann et al, 2018 ).…”
Section: Oxidative Stress and Periodontitismentioning
confidence: 99%